Epidemiology of extended spectrum beta-lactamase and carbapenemase-producing bacteria in stool from apparently healthy children, South Africa - Manenzhe, Rendani Innocent (Division of Medical Biochemistry, 2015)
Background: The prevalence of extended-spectrum beta-lactamase (ESBL) - and carbapenemase-producing Enterobacteriaceae in healthy humans in the community is largely unknown. We aimed to determine the prevalence and genetic characteristics of ESBL- and carbapenemase-producing Enterobacteriaceae in stools from healthy infants and their mothers, and to determine the risk factors associated with their carriage. Methods: This study was nested within the Drakenstein Child Health Study, a birth cohort in a semi-rural region of Western Cape Province, South Africa. Maternal and infants faecal samples (including the meconium) were collected at birth and at two additional time-points (5-12 and 20-28 weeks) from the infants only. Samples were screened for ESBLs and carbapenemase-producing organisms using ChromID ESBL and ChromID CARBA media, respectively. Identification of suspect ESBL/carbapenemase-producing isolates and antibiotic susceptibility were determined using the Vitek 2 system. ESBL production was confirmed using the combination disc test, and that of carbapenemase using the modified hodge test. Selected ESBL and carbapenemase genes were evaluated by the singleplex conventional polymerase chain reaction and Sanger sequencing. Risk factors were assessed by univariate analysis using the EPI Info version 7 software.